Strategic Knowledge Management in Micro Entreprises : From Tacit Know-how to Digital Readiness in Finnish Veterinary Clinics - Laitinen, Elisa (My University, 2025)
Micro-enterprises rely heavily on professional expertise and experiential know-how, making knowledge management (KM) both a strategic resource and a daily operational necessity. This study investigates how Finnish veterinary clinics create, share, and manage knowledge in their everyday work, and how these practices influence their digital and artificial intelligence (AI) readiness. The theoretical framework draws on literature related to KM processes, tacit and explicit knowledge, and digital readiness in micro-enterprises. The study adopts a qualitative research design to explore the dynamics of knowledge creation, sharing, and utilization within professional service settings. Empirical data were collected through five semi-structured interviews with clinic owners and managers. The data were analysed using thematic analysis, allowing both literature-informed and emergent themes to be identified and interpreted within the broader theoretical context. The findings indicate that KM in small veterinary clinics is primarily personal and informal, relying on individual routines, interpersonal communication, and situational problem-solving rather than formalized systems. Administrative fragmentation and time scarcity hinder the development of organizational KM practices, while strong professional autonomy both enables flexibility and limits standardization. The study concludes that digital transformation in micro-enterprises must begin with strengthening organizational KM capabilities, particularly documentation, data integration, and cultural readiness, before advanced AI solutions can be effectively adopted.
Keywords: Knowledge Management, Tacit Knowledge, Digital Readiness, Micro-Enterprises, Veterinary Clinics, Entrepreneurship, Artificial Intelligence